Penerapan Sertifikasi Laik Fungsi Terhadap Bangunan Publik di Kota Banda Aceh - A. Rani, Hafnidar; Hanif, Muhammad (University of Muhammadiyah Aceh, 2021)
Certificate of Occupancy (CO) is a certificate issued by the Regional Government for a building that has been completed and has met the requirements for the proper occupancy of the building, which is also applied to public buildings in Banda Aceh. The problem of this research is whether the building owner/user knows about CO and whether the building owner/user already knows about the implementation of CO in accordance with the law. This study aims to investigate the owner/users knowledge on CO and to determine the owner/users of the building knowledge about the application of CO in accordance with the law. The data collection technique was carried out by distributing questionnaires to 100 respondents, namely owners/users of public buildings in Banda Aceh. The variables used in this study are architectural components, structural, mechanical, electrical, outdoor layout, and the reliability of buildings to public buildings. The results of the factor analysis show that the correlation between a variable and the factors formed is > 0.5, so the factors formed have a relationship to summarize the six variables which has been analyzed. The results of the validity test of the r-table value of 0.197 meet the requirements of rcount > r table. The reliability test results qualify with Cronbach's Alpha value greater than 0.6. The results of descriptive analysis show that the frequency of building owners who know about CO is 6% and building users who know about CO is 2%, while the frequency of owners who know about the application of CO in accordance with the law is 2% and users who know about the application of CO are in accordance with the law is 1%. This indicates that there are still many users/owners of public buildings in Banda Aceh who do not know about CO and do not understand about the application of CO in accordance with the law. Therefore, the Banda Aceh Government needs to disseminate information about the implementation of CO, especially to owners of public buildings.